An optimisation model for cloud-based supply chain network design: case study in the banking industry. (8th July 2021) - Hajipour, Vahid; Niaki, Seyed Taghi Akhavan; Rahbarjou, Mohammad
New technologies provide tremendous integration opportunities not only for the flow of goods and services but also for managing information and financial data. Flexibility and agility are important metrics in organisations. Cloud technology can have a significant impact on improving flexibility and agility in organisations through faster data transfer between supply chain components. In this study, we present an optimisation model for cloud-based supply chain network design (SCND) problem by optimising the costs and quality of service (QoS). We present a case study in the banking industry to show the applicability and exhibit the efficacy of the proposed optimisation model.